EFFECT OF WATER STRESS ON SEED GERMINATION AND SEEDLING GROWTH IN SIX MEDICINAL PLANT SPECIES IN TARAI REGION, UTTARAKHAND - KANTA , CHANDRA; P. B. RAO, (The Bioscan, 2014)
The influence of water stress (0, -5, -10 and -15 bar) on seed germination and seedling growth in Lepidium sativum Linn., Spilanthes acmella Linn., Matricaria chamomilla Linn., Ammi majus Linn., Andrographis paniculata Nees., and Cassia tora Linn. in Tarai region of Uttarakhand, India were examined under laboratory conditions with triplicates. The per cent seed germination was maximum and minimum in 0 and – 15 bar water stress, respectively in all the species. The per cent germination was maximum (0 bar) in L. sativum (89.0) and minimum in M. chamomilla (46.0%). In high water stress (-15 bar), M. chamomilla was failed to germinateand it was 53.33 % in A. paniculata indicating more sensitive and tolerant species, respectively in comparison to other species. In the remaining species, radicle and plumule length (cm) and total seedling dry weight (mg) of 15 days old seedlings were reduced significantly with increasing water stress in all the species and the per cent reduction (percentage of maximum) was highest in C. tora (68.07), A. paniculata (81.27) and S. acmella (66.99), respectively. Thus, indicating that these species are more susceptible/intolerant to water stress compared to rest of the species.